الاشتراط في عقد الزواج - - مراد قصابي -جعفر سفاري (المسيلة, 2022)
يعتبر البحث في موضوع الاشتراط في عقد الزواج من المسائل الهامة في الوقت الحالي، وذلك لحاجة الناس إليه، من أجل تحقيق منافع ومصالح ضرورية لا يمكن تحقيقها بمجرد إبرام عقد الزواج، بل لابد من اشتراطها مسبقا والنص عليها في العقد، فكان لزاما تسليط الضوء حول دور المشرع الجزائري في مسايرته لمبدأ حرية الإشتراط في عقد الزواج، ومقارنته بالفقه الإسلامي، من حيث القيود والآثار المترتبة عليه، فقمنا بطرح الإشكالية التالية ما لمقصود بالاشتراط في عقد الزواج؟ و ما هي القيود والآثار الواردة عليه من منظور الفقه الإسلامي وقانون الأسرة الجزائري ؟. من خلال هذه الإشكالية بينا الضوابط الشرعية لمسألة الاشتراط في عقد الزواج من المنظور الفقهي، بإبراز الآراء الفقهية، التي منها ما كان مضيقا له وما مكان موسع له، وقارناها بالقيود التي نص عليها المشرع الجزائري ضمن قانون الأسرة، لنختم دراستنا بتبيان الآثار المترتبة عن مسألة الإشتراط في عقد الزواج من الناحية الفقهية والقانونية وعلى مستوى الإجتهاد القضائي. Research on the issue of stipulating the marriage contract is one of the important issues at the present time, due to the people’s need for it, in order to achieve necessary benefits and interests that cannot be achieved just by concluding the marriage contract. Rather, it must be stipulated in advance and stipulated in the contract, so it was necessary to shed light on the role of The Algerian legislator, in keeping with the principle of freedom to stipulate the marriage contract, and comparing it with Islamic jurisprudence, in terms of restrictions and the implications for it, we raised the following problem: What is meant by stipulation in the marriage contract? And what are the limitations and effects on it from the perspective of Islamic jurisprudence and Algerian family law? we explained the legal controls for the issue of stipulation in the marriage contract from the doctrinal perspective, by highlighting the jurisprudential opinions, including what was narrow for him and what was an expanded place for him, and we compared them with the restrictions stipulated by the Algerian legislator within the family law, to conclude our study by showing the implications of the issue of stipulation In the marriage contract in terms of jurisprudence and legal and at the level of jurisprudence.
Keywords: :الإشتراط، عقد الزواج، القيود، الآثار